Fixation Differences in Visual Search of Accident Scenes by Novices and Expert Emergency Responders. (December 2018) - Prytz, Erik G.; Norén, Caroline; Jonson, Carl-Oscar
Objective: We sought to investigate whether expert–novice differences in visual search behavior found in other domains also apply to accident scenes and the emergency response domain. Background: Emergency service professionals typically arrive at accidents only after being dispatched when a civilian witness has called an emergency dispatch number. Differences in visual search behavior between the civilian witness (usually a novice in terms of emergency response) and the professional first responders (experts at emergency response) could thus result in the experts being given insufficient or erroneous information, which would lead them to arrive unprepared for the actual situation. Method: A between-subjects, controlled eye-tracking experiment with 20 novices and 17 experts (rescue and ambulance service personnel) was conducted to explore expert–novice differences in visual search of accident and control images. Results: The results showed that the experts spent more time looking at task-relevant areas of the accident images than novices did, as predicted by the information reduction hypothesis. The longer time was due to longer fixation durations rather than a larger fixation count. Conclusion: Expert–novice differences in visual search are present in the emergency domain. Given that this domain is essential to saving lives and also relies heavily on novices as the first link in the chain of response, such differences deserve further exploration. Application: Visual search behavior from experts can be used for training purposes. Eye-tracking studies of novices can be used to inform the design of emergency dispatch interviews.